Wireless Catching and Transferring System of Next Generation Network - Huiqiu Li; Qin Chen; Xiaozheng Ning; Jian Huang; Zhide Li; Xuedan Zhang; Yuhan Dong (Dianxin kexue)
An wireless catching and transferring system of next generation network was introduced. With the advanced technology of IPv6, IEEE 802.11n and cloud computing, the system provided an effective solution, meeting the needs of professional journalists to catch and transfer quickly at large games and meetings.